Analisis Nilai Sosial dan Nilai Budaya pada Film “Air Mata di Ujung Sajadah” Karya Titen Wattimena serta Pemanfaatannya sebagai Bahan Pembelajaran Sastra di SMA - Ernawati, Ernawati (Universitas Mathla'ul Anwar Banten, 2024)
The background of the problem in this research is to describe social values in the form of the value of love, the value of responsibility and the value of harmony in life and Cultural Values in the form of cultural values in the relationship between humans and God, cultural values in the relationship between humans and society, cultural values in human relationships with other people, cultural values in human relationships with themselves, cultural values in human relationships with God in films, and their use in studying literature in high school. The method used in this research is a qualitative descriptive method. Meanwhile, the data source used in this research is a film entitled Air Mata Di Ujung Sajadah. From the source film there is 1 hour 45 minutes. Because by analyzing the social values and cultural values in the film it is in accordance with the literature learning material in high school. It is suggested that the results of this research can be presented as a reference for students in analyzing the social and cultural values in the film Tears at the End of the Prayer Mat by Titen Wattimena.